Aeromonas hydrophila subsp. dhakensis--a causative agent of gastroenteritis imported into the Czech Republic - Sedláček, Ivo; Krejčí, Eva; Andělová, Anna; Sedláčková, Michaela; Porazilová, Iva; Holochová, Pavla (Annals of agricultural and environmental medicine, 2012)
Out of the twenty-one A. hydrophila complex isolates obtained during a routine examination of human diarrhoeal faeces, two A. hydrophila subsp. dhakensis isolates (P1097 = CCM 7329 and P1165) were successfully identified by ribotyping. The correct taxonomic position of the A. hydrophila subsp. dhakensis CCM 7329 was verified by cpn60 sequencing (GeneBank accession number HM536193). The remaining A. hydrophila complex isolates were identified as A. hydrophila subsp. hydrophila. The ability of biochemical tests and fatty acid methyl ester analysis to reliably discern both A. hydrophila subsp. dhakensis and A. hydrophila subsp. hydrophila was limited. In contrast to the A. hydrophila subsp. hydrophila, the faecal isolates of A. hydrophila subsp. dhakensis did not produce acid from arbutin. When compared in a two-dimensional plot, the A. hydrophila subsp. dhakensis faecal isolates contained higher amounts of the two minor fatty acids C(13:0) and C(17:1) ω8c than the A. hydrophila subsp. hydrophila reference strain. This is the first detected occurrence of the less frequent A. hydrophila subsp. dhakensis in our region and ribotyping was proved as a suitable method for the identification of A. hydrophila subsp. dhakensis.
Keywords: Gram-Negative Bacterial Infections; průjem; feces; Humans; Ribotyping; Phylogeny; Sequence Analysis, DNA; Aeromonas hydrophila; Molecular Sequence Data; molekulární sekvence - údaje; Diarrhea; Phenotype; chaperonin 10; lidé; ribotypizace; bakteriální proteiny; Feces; sekvenční analýza DNA; mastné kyseliny; fylogeneze; fenotyp; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; Bacterial Proteins; Chaperonin 10; gramnegativní bakteriální infekce; Česká republika; Fatty Acids